Learning style and English vocabulary teaching in secondary school - Tsypanova, Nataliia (My University, 2016)
В даній статті розглядається використання найбільш сучасних методів навчання англійської лексики в середній школі. Показано, як вчитель має використовувати додаткові засоби навчання для досягнення найкращого результату. Ключовими концепціями статті є стилі навчання и додаткові засоби. Перша частина статті аргументує важливість збагачення словникового запасу учнів. Вказана частина пояснює як використовувати додаткові засоби і дає визначення додаткових засобів, що використовуються для навчання лексики. Друга частина зосереджена на різних стилях навчання і способах, якими учні отримують надану інформацію (візуальний, аудіальний, кінестетичний). Наведено приклад поєднання навчальних стилів для навчання учнів в школі. Показана ефективність подібного поєднання. В останній частині зроблені висновки і надані поради вчителям про найкращі практики в навчанні лексики. The article deals with the usage of the most up-to-date methods in English vocabulary teaching. It demonstrates how a teacher should use additional means of teaching in order to achieve the best result. The clue concepts the article dwells upon are learning styles and auxiliary aids. The article is aimed at teachers of secondary schools willing to increase efficiency of their work and diversify educational process. The first part of the article explains the importance of vocabulary enrichment for the students at all levels of English proficiency. The mentioned part explains how to use auxiliary aids and provides the definition of auxiliary aids used in vocabulary teaching. It demonstrates that as far as English vocabulary is rapidly growing and nowadays makes the greatest one among all human languages the teachers need even more effective means of teaching. Auxiliary aids are considered to be a powerful means of increasing the effectiveness of traditional means of vocabulary teaching. The second part concentrates on different learning styles and ways the students consume given information (visual, auditory and kinaesthetic). It provides an example of how learning styles are combined when teaching children at school. The efficiency of such combination demonstrated. An important thing such combination tends to achieve is synaesthesia – it greatly increases the efficiency of memorising of new information. The last part provides conclusions and tips for teachers about the best practices in vocabulary teaching. They can be introduced and widely used in secondary school for pupils with any level of English proficiency. That is the most powerful side of those practises – they are designed to be as universal as possible. This makes them widely applicable; teachers can also modify them in the way they see to be the best in their concrete case.
Keywords: додаткові засоби; навчальний стиль; поєднання навчальних стилів; auxiliary aids; learning style; learning style combination; кафедра ділової іноземної мови та міжнародної комунікації